Pseudo-Statolatry Among Salafi Wahhabi Groups Towards Law No. 52 of 2009 on Population Development and Family Planning: A Critical Study of the Debate on Birth Control as Limitation or Regulation - Najamudin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Salafi group rejects the government's policy on family planning with various theological and political arguments, while on the other hand this group claims to be an obedient citizen to the government. This research article aims to answer how the model of the rights and obligations of Salafi groups as citizens after the attitude of rejection of family planning policies. The method used in the study is descriptive legal research with a legalism approach. This study answers that the Salafi group considers the family planning policy as an effort to "limit births" while what is meant is "child regulation". The policy on family planning also gained legitimacy from scholars, even from Salafi scholars. Because the family planning policy has gained theological and political legitimacy, the Salafi group is obliged to comply with the policy by implementing rewards and punishments